2003
DOI: 10.1021/jf030016j
|View full text |Cite
|
Sign up to set email alerts
|

Patatin, the Tuber Storage Protein of Potato (Solanum tuberosum L.), Exhibits Antioxidant Activity in Vitro

Abstract: The potato (Solanum tuberosum L.) tuber storage protein, patatin, was purified to homogeneity with a molecular mass of 45 kDa. The purified patatin showed antioxidant or antiradical activity by a series of in vitro tests, including 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical (half-inhibition concentration, IC(50), was 0.582 mg/mL) scavenging activity assays, anti-human low-density lipoprotein peroxidation tests, and protections against hydroxyl radical-mediated DNA damages and peroxynitrite-mediated dihydrorh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 23 publications
2
81
0
Order By: Relevance
“…Patatin has also been shown to possess antioxidant or antiradical activity. Liu and colleagues [12] found that purified patatin exert antioxidant or antiradical activity in various in vitro tests, such as radical, scavenging activity assay and protection against hydroxyl radical-induced calf thymus DNA damage. Potato protein hydrolysates showed antioxidant activity [13] and enhanced oxidative stability of soybean oil emulsions [14].…”
Section: Biological Activities Of Plant Proteinsmentioning
confidence: 99%
“…Patatin has also been shown to possess antioxidant or antiradical activity. Liu and colleagues [12] found that purified patatin exert antioxidant or antiradical activity in various in vitro tests, such as radical, scavenging activity assay and protection against hydroxyl radical-induced calf thymus DNA damage. Potato protein hydrolysates showed antioxidant activity [13] and enhanced oxidative stability of soybean oil emulsions [14].…”
Section: Biological Activities Of Plant Proteinsmentioning
confidence: 99%
“…Potato storage proteins provide necessary nutrients for the development of tuber, mature-tosprouting tuber transition and successful plant growth [1][2][3][4]. The patatin is the major VSP of S. tuberosum, accounting for up to 45% of the total soluble protein [1,[4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The patatin is the major VSP of S. tuberosum, accounting for up to 45% of the total soluble protein [1,[4][5][6][7]. However, the molecular mechanism that triggers the cleavage of the patatin along the tuber life cycle has not to date been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Also several proteins are induced by diverse types of stress (Mehta et al, 1991) and similarly as phenols generate antiradical activities, i.e. health promoting effects in humans when consumed (Grace, 2005;Liu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%